(untitled) - Vesilind, P. Aarne (London, 1990)
Complex environmental problems are often reduced to an inappropriate level of simplicity. While this book does not seek to present a comprehensive scientific and technical coverage of all aspects of the subject matter, it makes the issues, ideas, and language of environmental engineering accessible and understandable to the nontechnical reader.
Keywords: Environmental engineering,Environment Pollution,Kỹ thuật môi trường,Ô nhiễm môi trường